Ecosystem‐level effects of a globally spreading invertebrate invader are not moderated by a functionally similar native. (30th June 2015) - Penk, Marcin; Irvine, Kenneth; Donohue, Ian; Dunn, Alison
Summary Biological invasions are a key element of human‐induced global environmental change. However, lack of knowledge of the indirect consequences of invasions, combined with poor understanding of how their ecological effects depend upon competitive attributes of the receiving community, hinders our ability to manage and predict the effects of invasive species on ecosystems. We established an experiment using a combination of both additive and substitutive experimental designs to explore the effects of the globally spreading mysid shrimp Hemimysis anomala on the biological structure of outdoor pond mesocosms in the absence and presence of a functionally similar native competitor, Mysis salemaai. The naturally smaller H. anomala had considerably stronger effects on primary producers, multiple aspects of consumer assemblages and overall biological structure of the ponds in comparison with the functionally similar native. Moreover, the magnitude of these effects was generally independent of the presence of M. salemaai and even total mysid density. Hemimysis anomala reduced both the abundance and diversity of zooplankton assemblages significantly, triggering a strong trophic cascade on phytoplankton and a simultaneous increase of benthic invertebrate biomass. These findings indicate that invasion by H. anomala may exacerbate the effects of nutrient enrichment on lakes. Our results demonstrate that introduced species can, irrespective of the presence of functionally similar natives, induce complex changes to ecosystems that reach beyond direct consumptive effects. Moreover, the cascading indirect effects of invasion can exacerbate the impacts of other stressors. Disregarding the complexity of indirect effects therefore risks underestimating significantly the global ecological footprint of biological invasions.